Critical points halal of fermented beverage products - Pintaito, Zahra Abidina; Hanafiah, Intan (Journal of Halal Science and Research, 2025)
Public awareness of the importance of health is increasing, leading to higher consumption of functional products such as fermented beverages. Kombucha, kefir, and fermented milk are among the most popular fermented products. However, several aspects can become critical points for ensuring their halal status. This paper aims to identify the halal-critical points of fermented beverages, particularly kombucha, kefir, and fermented milk, with a focus on the use of starter cultures and their impact on the final product. A common critical point across these products is the fermentation duration, which directly affects alcohol content. According to Fatwa MUI No. 10 of 2018, fermented products remain halal if the alcohol content does not exceed 0.5%. For kombucha and water kefir, the critical points lie in the halal status of the water and sugar used, as well as the source of the starter culture or SCOBY in kombucha. In the case of milk kefir and fermented milk, the type and source of milk represent critical points. Furthermore, microbial sources and growth media derived from non-halal or impure materials are also considered critical points, as regulated under MUI Fatwa No. 01 of 2010.Keywords: Alcohol content, Fermented beverages, Halal.